Computation of External view based Software Metrics: Java Based Tool - Powar, PL; Singh, MP; Solanki, Bharat; Wasat Shareef, Jawwad (International Journal of Computer Sciences and Engineering, 2025)
Component based software development (CBSD) strategies have been found to be boon for software development companies. The contribution of past researches in the area of software cost estimation of component based software development was excellent. It has been noticed that the use of the components in software development is hierarchical and this multilevel implementation increases the complexity of the software development. If the depth of the components in hierarchy and their association and aggregation with each other are available in advance then this information helps in estimating the cost and complexity of the software in early stage. The present paper compute the different metrics values during the design phase of the entire life cycle of software development. A component diagram consisting of the various components and their associations has been prepared using ArgoUML software tool. Considering a case of E-learning, our technique has been implemented on this special case, to compute various metrics for analyzing certain results of the software at designing stage which turns out to be the important information to control the development cost and the complexity of the software in advance. By computing external view based metrics we can assess effort estimation and complexity of CBSE at early stage.